The knowledge filter, entrepreneurship, and economic growth - Bo Carlsson; Zoltán J. Ács; David B. Audretsch; Pontus Braunerhjelm (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This paper explores the relationship between knowledge creation, entrepreneur-ship, and economic growth in the United States over the last 150 years. Accor-ding to the new growth theory, investments in knowledge and human capital ge-nerate economic growth via spillovers of knowledge. But the theory does not ex-plain how or why spillovers occur, or why large investments in R&D do not al-ways result in economic growth. What is missing is the knowledge filter - the distinction between general knowledge and economically useful knowledge. Also missing is a mechanism (such as entrepreneurship) converting economically re-levant knowledge into economic activity. This paper shows that the unpreceden-ted increase in R&D spending in the United States during and after World War II was converted into economic activity via incumbent firms in the early postwar period and increasingly via new ventures in the last few decades.
Keywords: O14; O17; O30; N90; 330; knowledge; economic growth; entrepreneurship; spillovers; history; Wissenstransfer; Unternehmer; Wirtschaftswachstum; Neue Wachstumstheorie; USA